Selection of sports news portal with analytical hierarchy process (AHP) method - Wulan Dari; Michael Taroreh (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
The world of sports, often becomes the main attraction for the audience. Apart from the euphoria of athletes and idolized clubs when competing, especially when the national team is competing. As if to be an attraction and unifier of all groups. Therefore, there is a sports news portal as a digital information bridge to make it easier for the public to access information. From the several sports news portal pages, it is hoped that readers can choose the best sports news portal according to their needs. Therefore, there is the Anatical Hierarchy Process (AHP) as a research method used to solve complex problems from a problem based on predetermined criteria and alternatives. From the results of this study, it succeeded in producing the standings in the first position occupied by Bolasport with 40.5% achievement, followed by Indosport 30.2% and detiksport 28.7%